Access to Finance and Risk Financial Attitude: Bridging Financial Literacy with MSME Sustainability - Cahyaningtyas, Susi Retna; Karim, Nina Karina; Lenap, Indria Puspitasari; Yunita, Alma (PT. EQUATOR SINAR AKADEMIA, 2025)
This study aims to examine the direct effect of financial literacy and sustainability on micro, small, and medium enterprises (MSMEs) in Mataram, Indonesia. The study also analyzes the mediating effect of access to finance and financial risk attitude on the relationship between financial literacy and sustainability in MSMEs in Mataram, Indonesia, supported by the Resource-Based View (RBV), Knowledge-Based View (KBV), Pecking Order Theory, and Dual Process Theory. In addition, this study uses a descriptive quantitative methodology, where questionnaires were distributed to MSME practitioners in Mataram, and the data were analyzed using Structural Equation Model Partial Least Square (SEM-PLS). The findings indicate a positive relationship between financial literacy, access to finance, and financial risk attitude towards sustainability in MSMEs in Mataram. Furthermore, there is a significant effect of access to finance and financial risk attitude as mediators in the relationship between financial literacy and sustainability. Therefore, this study provides valuable insights for MSME practitioners to improve their financial knowledge and skills to support business growth and sustainability.